Erythropoietin and diabetes mellitus - Maiese, Kenneth (World J Diabetes, 2015)
Erythropoietin (EPO) is a 30.4 kDa growth factor and cytokine that governs cell proliferation, immune modulation, metabolic homeostasis, vascular function, and cytoprotection. EPO is under investigation for the treatment of variety of diseases, but appears especially suited for the treatment of disorders of metabolism that include diabetes mellitus (DM). DM and the complications of this disease impact a significant portion of the global population leading to disability and death with currently limited therapeutic options. In addition to its utility for the treatment of anemia, EPO can improve cardiac function, reduce fatigue, and improve cognition in patients with DM as well as regulate cellular energy metabolism, obesity, tissue repair and regeneration, apoptosis, and autophagy in experimental models of DM. Yet, EPO can have adverse effects that involve the vasculature system and unchecked cellular proliferation. Critical to the cytoprotective capacity and the potential for a positive clinical outcome with EPO are the control of signal transduction pathways that include protein kinase B, the mechanistic target of rapamycin, Wnt signaling, mammalian forkhead transcription factors of the O class, silent mating type information regulation 2 homolog 1 (Saccharomyces cerevisiae), and AMP activated protein kinase. Therapeutic strategies that can specifically target and control EPO and its signaling pathways hold great promise for the development of new and effective clinical treatments for DM and the complications of this disorder.